(untitled) (The Journal of Psychology and Sociology, 2024)
In the context of rapid changes occurring in the economy and geopolitics, we are faced with the task of studying conceptual approaches to defining the term repatriate for ethnic Kazakhs, as well as identifying social factors of their adaptation. The purpose of the study was to determine the relevance of the introduction of the term "kandas" and its preference over the term "oralman", as well as to identify factors of social adaptation using the quantitative method of sociological survey. Research question: do different categories of respondents agree with the introduction of the new term "kandas" instead of the term "oralman"? The main conclusions of the study confirm the following hypotheses: • For ethnic Kazakhs returning to their historical homeland, the term "kandas" is more suitable than the term "oralman". • Gender of kandases does not affect the preferences of communication with them among citizens of Kazakhstan. • The age of the kandases does not affect the preferences of communication with them among citizens of Kazakhstan. • The settlement of the kandases in the northern regions of Kazakhstan is more favorable. During the period from July 20, 2022 to March 20, 2023, a sociological questionnaire survey was conducted in written form by contact communication through the delivery of questionnaires to respondents, as well as from April 3, 2023 to June 9, 2023 in the form of a contactless online survey using a Google form on the territory of the Republic of Kazakhstan. As a result of the study, respondents’ preferences in communicating with kandas by gender and age were identified, as well as the optimal region in the settlement of kandas. The scientific value of the study lies in the confirmation of the hypotheses put forward, which are a scientific novelty in the field of kandases’ immigration. The practical significance of the research results lies in the use of the results of a sociological survey for practical recommendations on the integration of kandas in the north of Kazakhstan. Key words: kandas, migration, social adaptation.